Building sustainability indicators: state-of-the-art and challenges for development in Brazil - Silva, Vanessa Gomes da (ANTAC - Associação Nacional de Tecnologia do Ambiente Construído, 2008)
Sustainability indicators of the built environment describe its environmental, economic and social impacts for designers, owners, users, managers, policy makers and other stakeholders from the building sector. Such indicators capture trends to inform decision agents, guide policies and strategies development and monitoring, among other roles. Sustainability indicators rose initially at the nations’ sphere, most of them in response to Agenda 21, but sustainability metrics are necessary at all levels. In Brazil, there are several efforts to define sustainability metrics for the built environment at different scales. However, the existing metrics vary greatly, being defined by criteria and methodologies that are not necessarily replicable. This paper has four major goals: to revise international literature and define sustainability indicators; to stimulate a strategic reflection on difficulties and barriers for the establishment of sustainability indicators for the built environment in Brazil; to identify research needs to promote effective advance in this field; and to discuss methodological procedures to develop indicators at the building level. A set of guidelines for developing sustainability indicators is proposed: (a) define a framework and methodology for developing sustainability indicators; (b) define common indicators to be monitored at national level, as well as groups of local indicators, selected as appropriate; (c) create a national database; and (d) make these data publicly available and up-to-date.